The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.chembiol.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Basis for Intracellular Kinase Inhibition by Src-specific Peptidic Macrocycles

Abstract: Protein kinases are attractive therapeutic targets because their dysregulation underlies many diseases, including cancer. The high conservation of the kinase domain and the evolution of drug resistance, however, pose major challenges to the development of specific kinase inhibitors. We recently discovered selective Src kinase inhibitors from a DNA-templated macrocycle library. Here, we reveal the structural basis for how these inhibitors retain activity against a disease-relevant, drug-resistant kinase mutant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The two structures reported here represent the first reported X-ray crystal structures with pNO 2 F incorporated into a protein structure using the amber codon-suppression technology. Previous structures containing the pNO 2 F residue contained pNO 2 F on a synthesized short peptide fragment (4-8 residues; Rose et al, 1996;Lizak et al, 2011;Aleem et al, 2016;Napió rkowska et al, 2017) or a semi-synthetic protein in which the pNO 2 F was synthesized in a peptide that was later ligated to an expressed protein fragment (Baril et al, 2017). The Asp133pNO 2 F sfGFP and Asn149pNO 2 F sfGFP crystal structures illustrate clear density for the pNO 2 F residue at the specified position, indicating that pNO 2 F can be sitespecifically incorporated to produce a stable pNO 2 F group.…”
Section: Tablementioning
confidence: 99%
“…The two structures reported here represent the first reported X-ray crystal structures with pNO 2 F incorporated into a protein structure using the amber codon-suppression technology. Previous structures containing the pNO 2 F residue contained pNO 2 F on a synthesized short peptide fragment (4-8 residues; Rose et al, 1996;Lizak et al, 2011;Aleem et al, 2016;Napió rkowska et al, 2017) or a semi-synthetic protein in which the pNO 2 F was synthesized in a peptide that was later ligated to an expressed protein fragment (Baril et al, 2017). The Asp133pNO 2 F sfGFP and Asn149pNO 2 F sfGFP crystal structures illustrate clear density for the pNO 2 F residue at the specified position, indicating that pNO 2 F can be sitespecifically incorporated to produce a stable pNO 2 F group.…”
Section: Tablementioning
confidence: 99%
“…Despite its modest size compared with subsequent industrial DNA-encoded libraries 9, 11, 42 , this initial library was of sufficient quality and diversity to serve as a source of potent and selective inhibitors of proteins including kinases and insulin-degrading enzyme (IDE) protease, ultimately leading to biological discoveries and the validation in vivo of new targets for therapeutic intervention. 4346 …”
mentioning
confidence: 99%
“…The MDA-MB-231 cells rely on Src signalling for cell migration and metastasis ( Figure 4 b). ( 44 , 45 ) We observed that 4 inhibits the autophosphorylation of Src in the cell ( Figure 4 d) and significantly impaired the wound healing rates (IC 10 and IC 50 dose) ( Figure S8b-c ). The migration process involves the TNF-α induced activation of Src signalling cascade and translocation of ERK1/2 to the nucleus.…”
Section: Resultsmentioning
confidence: 87%